Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1186/s12888-021-03358-0
|View full text |Cite
|
Sign up to set email alerts
|

Associations between symptom severity and well-being among Thai patients with schizophrenia: a cross-sectional analytical study

Abstract: Background Severity of symptoms in patients with schizophrenia is a determinant of patient’s well-being, but evidence in low- and middle-income countries is limited. We aimed to measure the symptom severity using objective measurements, the Brief Psychiatric Rating Scale (BPRS) and Clinical Global Impression-Severity scale (CGI-S), and their associations with well-being in patients with schizophrenia. Methods Patients with schizophrenia aged ≥18 ye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The current study linked the extracted features from rs-fMRI od SZ, BP, and SAD with clinical scores using partial correlation analysis. Many studies have found a link between basic clinical parameters and psychotic traits (mainly focused on SZ disorder) (Hudgens-Haney et al, 2020; Bian et al, 2021; Chu et al, 2021; Huo et al, 2021; Pelizza et al, 2021; Targum et al, 2021; Teetharatkul et al, 2021). These studies are based on group-level data rather than individual patient data (Ozomaro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…The current study linked the extracted features from rs-fMRI od SZ, BP, and SAD with clinical scores using partial correlation analysis. Many studies have found a link between basic clinical parameters and psychotic traits (mainly focused on SZ disorder) (Hudgens-Haney et al, 2020; Bian et al, 2021; Chu et al, 2021; Huo et al, 2021; Pelizza et al, 2021; Targum et al, 2021; Teetharatkul et al, 2021). These studies are based on group-level data rather than individual patient data (Ozomaro et al, 2013).…”
Section: Discussionmentioning
confidence: 99%